New Zealand’s Accident Compensation Scheme and Man-Made Disease - Hook, Maria (Victoria University of Wellington Law Review, 2008)
This paper proposes that cover provided for "personal injury" within the current Injury Prevention, Rehabilitation, and Compensation Act 2001 should be extended to include man-made disease. The concept of man-made disease is used to distinguish between naturally occurring diseases and diseases that are predominantly caused by human activities. An analysis of the existing principles within the accident compensation scheme reveals that such an amendment is supported by three principles in particular: the replacement of the right to sue for personal injury, community causal responsibility and prevention. It is argued that as well as introducing long-needed consistency into the scheme, cover for man-made disease would remedy some of the problems regarding compensation for work-related diseases.